Beliefs About Children’s Memory and Child Investigative Interviewing Practices: A Survey in Dutch Child Protection Professionals from ‘Safe Home’ - Erens, Brenda; Otgaar, Henry; Patihis, Lawrence; de Ruiter, Corine (Frontiers in Psychology, 2020)
Knowledge of children’s memory and forensic interviewing skills are crucial in child abuse investigations. Safe Home is the Dutch hotline where both professionals and citizens can report concerns about child abuse or domestic violence. Professionals at Safe Home often serve as first responders to determine the need for a child abuse investigation, protective measures and/or further police investigation. In this study, child protection professionals (N = 158) employed at Safe Home (i.e., behavioral scientists, medical doctors, and social workers) completed an online survey on beliefs about memory functioning and forensic interviewing. In line with earlier studies, we expected to find a lack of knowledge about memory functioning among Safe Home workers. Furthermore, we expected limited use of evidence-based forensic interviewing methods. Indeed, we found many professionals endorsed beliefs not in line with current memory research, especially beliefs about repressed and recovered memories. Still, high percentages of professionals also reported memory beliefs related to false memory formation and suggestion, that were in line with scientific evidence. Some professionals reported using interviewing methods for which there is no empirical validation. Because child protection professionals are often the first to interview children about allegations of abuse, the current findings identify a need for training in child forensic interviewing, including knowledge of human memory.